1998
DOI: 10.1093/qjmed/91.12.845
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmoscopic abnormalities in adults with falciparum malaria

Abstract: We studied 424 adults with falciparum malaria admitted over 28 months. They were divided into three groups: cerebral malaria (n = 214); severe non-cerebral malaria (n = 58); and uncomplicated malaria (n = 152). Fundus examination was done daily from admission to discharge, and weekly thereafter in those with persistent changes. All patients were treated by a protocol based on WHO guidelines. Ophthalmoscopic abnormalities were: retinal haemorrhages, 40 (9.43%) (25 cerebral malaria, 10 severe non-cerebral and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 1 publication
1
32
0
Order By: Relevance
“…Earlier in a similar study done in adult patients of falciparum malaria in the same region, Kochar et al had found ophthalmoscopic findings to be present in 34% cases of cerebral malaria, 24% cases of non-cerebral severe malaria, and 12% cases of uncomplicated malaria. 13 Another study on adults with severe falciparum malaria in Bangladesh (a low transmission area) found retinal changes to be present in 14 of 20 patients with cerebral malaria, 3 of 7 patients with non-cerebral severe malaria, and 3 of 15 patients with uncomplicated malaria. 12 In comparison studies, in children by Beare et al and Essuman et al found retinopathy in 53% children with non-cerebral severe malaria due to P. falciparum in Malawi and Ghana, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier in a similar study done in adult patients of falciparum malaria in the same region, Kochar et al had found ophthalmoscopic findings to be present in 34% cases of cerebral malaria, 24% cases of non-cerebral severe malaria, and 12% cases of uncomplicated malaria. 13 Another study on adults with severe falciparum malaria in Bangladesh (a low transmission area) found retinal changes to be present in 14 of 20 patients with cerebral malaria, 3 of 7 patients with non-cerebral severe malaria, and 3 of 15 patients with uncomplicated malaria. 12 In comparison studies, in children by Beare et al and Essuman et al found retinopathy in 53% children with non-cerebral severe malaria due to P. falciparum in Malawi and Ghana, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, retinal changes in adults with severe falciparum malaria (both cerebral and non-cerebral) have also been described from this region. [12][13][14] There have been few isolated case reports regarding eye changes in cases of vivax malaria including retinal hemorrhages. [15][16][17][18] The presence of retinal changes assumes the importance in light of increased recognition of severe disease in vivax malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Here, ocular disease certainly follows this pattern, as the most-common ocular finding in malaria is retinal hemorrhage and is thought to be a consequence of anemia (149). Other eye-related findings include amaurosis fugax, optic neuritis, glaucoma, panuveitis, oculomotor paralysis, and cortical blindness.…”
Section: Ocular Disease Caused By Protozoansmentioning
confidence: 94%
“…Luvira V et al also reported a case of cerebral venous thrombosis in a Thai patient. 28 30 Another study by Looareesuwan S et al showed haemorrhage in 14.5% in 1983. 31 Kochar et al observed papilloedema in 5.5% cases.…”
mentioning
confidence: 98%